The Geometric Phases and Quasienergy Spectral Series of a Hartree-Type Equation with a Quadratic Potential; Russian Physics Journal; Vol. 47, iss. 4 - Lisok A. L. Aleksandr Leonidovich; Litvinets F. N.; Trifonov A. Yu. Andrey Yurievich; Shapovalov A. V. Aleksandr Vasilyevich (2004, 2004)
Title screen